Citrus Foliar Fungal Diseases for the Dooryard - Megan M. Dewdney; Jamie D. Burrow (EDIS, 2019)
This document is a two-page illustrated identification sheet for citrus foliar fungal diseases. It is a minor revision written by Megan M. Dewdney and Jamie D. Burrow, and published by the Plant Pathology Department, February 2019.